Palmetto Tortoise Beetle, Florida Tortoise Beetle (unofficial common names), Hemisphaerota cyanea (Say), (Insecta: Coleoptera: Chrysomelidae: Cassidinae) - Donald W. Hall; Jerry F. Butler (EDIS)
The Florida tortoise beetle is recorded from Florida, Georgia, Alabama, and Texas, and also probably occurs in Louisiana and Mississippi in areas where palms grow. This document is EENY-232, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001.